Pathways to transform urban food systems: feminist action research from Cape Town and Nairobi - Nicole Paganini; Vanessa Farr; Jes Weigelt (Frontiers in Sustainable Food Systems)
This paper offers a feminist reflection on the findings of an ongoing study of health and wellbeing associated with urban food security in Nairobi and Cape Town. It offers five pathways through which a strengthened informal sector can contribute to transforming urban food systems: identifying stronger entry points for institutionalized collaboration between local governments and community-based organizations; enhancing government capacities to collaborate with grassroots actors; the potential, and challenges, of controlled-environment agriculture; rethinking and shifting the regulatory environment surrounding the informal economy; and responding to detailed new data on the state of food security in South African informal settlements. Conducted in partnerships between the Urban Food Futures program and people who were permanently displaced during the colonial era, the study is informed by an emerging body of analysis that responds to the complex trauma of undernutrition, and approaches health as something far beyond an individual’s own somatic/bodily state of being. Participation in the study enabled communities living in a near-permanent state of precarity and food insecurity, in the absence of culturally appropriate and readily-available supports to mental health, to move beyond an isolated focus on food to explore feelings of psychic safety and security, and also environmental wellbeing, including access to clean air and water, decent and affordable housing, safe and dignified work, and freedom from violence of all forms.